(untitled) (Annals of Medical Research, 2025)
Aim: Tumor necrosis factor-alpha (TNF-α) plays a significant role in the pathogenesis of inflammatory bowel disease (IBD) and is associated with atherosclerosis and dyslipidemia. Despite the established use of anti-TNF-α antagonists in the treatment of IBD, the impact of these drugs on lipid profiles remains unclear, with conflicting evidence in the literature. Our study aims to assess the effect of anti-TNF treatment on lipid profile in pateints with IBD. Materials and Methods: Lipid profiles, including total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), triglycerides, and the atherogenic index, were measured in 103 patients (66 patients with CD, 37 with UC) at baseline and at 12 and 24 weeks of TNF-α inhibitor treatment, and the results were compared between the groups. Results: No significant change in cholesterol levels was observed over the course of 24 weeks (p=0.349). However, a noteworthy increase in HDL levels was observed from baseline to 24 weeks (p=0.016). No significant alterations in LDL and triglyceride levels were noticed over 24 weeks. The atherogenic index demonstrated no significant changes over the treatment period (p=0.462). Conclusion: Anti-TNF-α therapy, either with infliximab or adalimumab, among patients with IBD does not lead to a considerable alteration in lipid profiles after 3 and 6 months of treatment, with the exception of a significant increase in HDL.